2011
DOI: 10.1007/s13105-011-0123-1
|View full text |Cite
|
Sign up to set email alerts
|

NAD(P)H oxidase inhibiting with apocynin improved vascular reactivity in tail-suspended hindlimb unweighting rat

Abstract: Recent studies suggested that reactive oxygen species derived from nicotinamide adenine dinucleotide phosphate (NAD(P)H) oxidase is of functional importance in modulating vascular tone, and we have previously detected excessive superoxide production in tail-suspended hindlimb unweighting (HU) rat cerebral and carotid arteries. HU rat was a widely used model to simulate physiological effects on the vasculature. The present study tended to investigate whether NAD(P)H oxidase inhibition with apocynin influences v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 21 publications
1
30
0
Order By: Relevance
“…However, this latter finding contradicts a reported increase in NO following apocynin 47, 48 . It is possible that the relatively short time allowed after acute apocynin administration in our study accounts for such discrepancy because NO decreases and increases following acute (minutes) and extended (hours/days) exposure to apocynin 49 .…”
Section: Discussionmentioning
confidence: 82%
“…However, this latter finding contradicts a reported increase in NO following apocynin 47, 48 . It is possible that the relatively short time allowed after acute apocynin administration in our study accounts for such discrepancy because NO decreases and increases following acute (minutes) and extended (hours/days) exposure to apocynin 49 .…”
Section: Discussionmentioning
confidence: 82%
“…Studies have also shown that changes in NADPH oxidase expression can mediate radiation-induced oxidative stress in rat brain microvascular endothelial cells (56). Furthermore, a recent study demonstrated that NADPH oxidase-derived oxidative stress mediated abnormal vascular reactivity in hindlimb unloaded rats (21). FIG.…”
Section: Simulated Spaceflight Induces Oxidative Damage In Brainmentioning
confidence: 97%
“…Studies have shown that both microgravity encountered by astronauts in space, as well as modeled microgravity on Earth, can induce many deleterious physiological effects including changes in brain structure and function (20). As with radiation, one of the mechanisms involved in the response to spaceflight is oxidative stress (21,22). Studies have shown that exposure to microgravity during space flights is associated with increased oxidative stress markers reflecting damage to lipids, including lipid peroxidation, in the brain of both humans and rodents (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…of the upper body region, whereas there are atrophic adaptations and reduced contractile responsiveness in arteries of the lower body region (Tuday et al 2007;Lin et al 2009;Zhang et al 2012;Behnke et al 2013;Taylor et al 2013). For the large and elastic conduit arteries, it is reported that simulated microgravity induced an increase in blood pressure and flow in the common carotid artery of rats (Zhang 2013).…”
Section: Vascular Remodeling During Real/simulated Microgravitymentioning
confidence: 99%
“…We have previously demonstrated that simulated microgravity induced hypertrophic changes and increased the expression levels of ROS and VCAM-1 in the common carotid artery of rats (Zhang et al 2008(Zhang et al , 2009. We have also reported that simulated microgravity activated the angiotensin II (Ang II)/angiotensin type 1 receptor (AT1) signaling pathway and induced the nicotinamide adenine dinucleotide phosphate (NADPH) oxidase-derived oxidative stress in the common carotid artery of rats (Zhang et al 2012), all of which suggested that there may be an inflammatory response in the common carotid artery of rats exposed to simulated microgravity.…”
Section: Vascular Remodeling During Real/simulated Microgravitymentioning
confidence: 99%